Pengaruh Keselamatan dan Kesehatan Kerja (K3) dan Lingkungan Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Mediasi pada PT. Subur Baru Madani Rokan Hulu - Asyroful Munawar; Sehani Sehani (Yayasan Almanar Pujud, 2025)
This study aims to analyze the influence of Occupational Safety and Health (OHS) and the work environment on employee performance, with job satisfaction as a mediating variable at PT Subur Baru Madani Rokan Hulu. The method used was a quantitative approach, collecting data through questionnaires from the entire employee population (42 respondents) using a census technique. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) version 4.0. The results showed that OHS and the work environment had a positive and significant effect on employee performance. OHS and the work environment also had a significant effect on job satisfaction. Furthermore, job satisfaction was shown to mediate the relationship between OHS and the work environment on employee performance. OHS, the work environment, and job satisfaction variables explained 96% of employee performance.